CBS News/New York Times National and Local Surveys, 1985 ([Verlag nicht ermittelbar], 1986)
The substantive common denominator in the surveys is a continuing evaluation of the Reagan presidency. Each survey also contains questions of topical relevance or questions about broader social issues. Respondents were queried about their attitudes towards the arms race and "Star Wars", Ronald Reagan and his domestic and foreign policies, tax reform, the federal deficit, the Vietnam War, Reagan's visit to the military cemetery in Bitburg, Central America, trade policies, the United Nations, AIDS, the Soviet Union, and religion and the Catholic church. One survey contains questions concerning race relations and public figures in New York City. Only New York City residents were interviewed for this particular survey. All surveys contain demographic information on respondents.